Determinan belanja modal provinsi di Indonesia: pendekatan analisis ekonomi dan sosial - Rahmadi, Selamet (Jurnal Paradigma Ekonomika, 2025)
This research aims to measure and analyze the influence of Regional Original Income, Tax Revenue Sharing Funds, GRDP, Human Development Index, Poverty Rate, and Open Unemployment Rate on Capital Expenditure in all Provinces in Indonesia. This study uses secondary data in the form of a Cross-Section period 2015-2023. The analytical tool used is semi-logarithmic panel data regression. Based on the measurement results, the influence value of various independent variables on the dependent variable is obtained. Regional Original Income, Tax Revenue Sharing Funds, GRDP, and the Human Development Index have a significant effect on capital expenditure. Meanwhile, the poverty rate and open unemployment rate do not have a significant effect on capital expenditure.